Immunohistochemistry Analysis of CD44, EGFR, and p16 in Oral Cavity and Oropharyngeal Squamous Cell Carcinoma. (August 2017) - Cohen, Erin R.; Reis, Isildinha M.; Gomez, Carmen; Pereira, Lutecia; Freiser, Monika E.; Hoosien, Gia; Franzmann, Elizabeth J.
Objectives: We analyze the relationship between CD44, epidermal growth factor receptor (EGFR), and p16 expression in oral cavity and oropharyngeal cancers in a diverse population. We also describe whether particular patterns of staining are associated with progression-free survival and overall survival. Study Design: Prospective study, single-blind to pathologist and laboratory technologist. Setting: Hospital based. Subjects and Methods: Immunohistochemistry, comprising gross staining and cellular expression, was performed and interpreted in a blinded fashion on 24 lip/oral cavity and 40 oropharyngeal cancer specimens collected between 2007 and 2012 from participants of a larger study. Information on overall survival and progression-free survival was obtained from medical records. Results: Nineteen cases were clinically p16 positive, 16 of which were oropharyngeal. Oral cavity lesions were more likely to exhibit strong CD44 membrane staining ( P = .0002). Strong CD44 membrane and strong EGFR membrane and/or cytoplasmic staining were more common in p16-negative cancers ( P = .006). Peripheral/mixed gross p16 staining pattern was associated with worse survival than the universal staining on univariate and multivariate analyses ( P = .006, P = .030). This held true when combining gross and cellular localization for p16. For CD44, universal gross staining demonstrated poorer overall survival compared with the peripheral/mixed group ( P = .039). CD44 peripheral/mixed group alone and when combined with universal p16 demonstrated the best survival on multivariate analysis ( P = .010). Conclusion: In a diverse population, systematic analysis applying p16, CD44, and EGFR gross staining and cellular localization on immunohistochemistry demonstrates distinct patterns that may have prognostic potential exceeding current methods. Larger studies are warranted to investigate these findings further.